Biopharmaceutical Properties of New Mucoadhesive Dosage Form for Eye Degenerative Diseases Treatment - M. N. Anurova; E. O. Bakhrushina; I. V. Lapik; A. R. Turaeva; N. B. Demina; B. B. Sysuev; I. I. Krasnyuk (Разработка и регистрация лекарственных средств, 2023)
Introduction. Degenerative retinal diseases, including glaucoma, are the main cause of vision loss in the adult population. The development and improvement of drug treatment of this group of diseases is an urgent problem.Aim. Study of a new dosage form of methylethylpyridinol in the form of an ophthalmic gel.Materials and methods. The objects of the study were samples of eye gels containing methylethylpyridinol, for which mucoadhesion was studied by a combination of in vitro / ex vivo methods. Biodegradation and release kinetics of the active substance from the dosage form were studied using a dissolution tester in an artificial tear fluid medium. The shelf life of the dosage form was established in accordance with the stability study program. Determination of the local irritative action was carried out by conjunctival test in 10 rabbits of chinchilla breed weighing 3,6–4,1 kg.Results and discussion. The article presents the results of the study of biopharmaceutical characteristics of the previously developed ophthalmic gel of methylpyridinol based on a nonionic polymer – hydroxyethylcellulose brand Natrosol™ 250 HHX. A comparative study of mucoadhesion by in vitro / ex vivo flow of ophthalmic gel samples in the range of hydroxyethylcellulose concentration in the gel of 1–1.5 % was performed. The sample with 1.5 % polymer content had the best adhesive characteristics because it had a minimum flow rate: in vitro 2.7 · 106 m/s and ex vivo 2.3 · 106 m/s. Dissolution kinetics and visual biodegradation of the sample after "Dissolution" test were studied, which indicates prolonged release of methyl ethyl pyridinol from the gel. The stability of the developed dosage form under long-term and stress conditions was shown. The local irritating effect was estimated by the conjunctival test.Conclusion. The main biopharmaceutical characteristics of the developed ophthalmic gel methylpyridinol were determined and it was shown that it can be used as a delivery system for the treatment of degenerative retinal diseases because it possesses marked bioadhesive properties and prolonged release. The shelf life of the dosage form was determined, which was 2 years. Stress studies of methylethylpyridinol gel were carried out. The developed ophthalmic gel has no local irritating effect.